Human security, cultural integrity, and development the Manobo case - Calara, Alvaro N. (2020)
The long history of colonization and encroachment spurred growth and development in almost all parts of the world. Lagging, however, is the continuous struggle of the indigenous peoples (IPs) and indigenous cultural communities (ICCs) for a better life, most of whom are still at the brink of basic survival. In the case of the Philippines, the Republic Act 8371 also knows as the Indigenous Peoples' Rights Act (IPRA) of 1997 enshrined the IPs' rights to their ancestral lands and domain, self-governance and empowerment, social justice and human rights and cultural integrity.

In cases where the pursuit of development impinges upon the IPs/ICCs' cultural heritage, securing their cultural integrity is primordial and must be prioritized. A dialogic approach is always ideal to engage IPs/ICCs in any development process.

Using Berry's Acculturation Model, the study describes the participation of the Manobos in Bukidnon in a community consultation undertaken by NCIP Region X in the municipalities of Dangcagan and Kibawe as part of the development process being pursues by the province. As it highlights the best practices during the consultation, it also underscores ramifications of the development prospect among the Manobos in the province of Bukidnon.
Keywords: Human security; Cultural identity; Indigenous rights; Indigenous peoples; Manobos (Philippine people)